Estudo do acoplamento estrutural de variáveis micrometeorológicas pelo método da rotação do espaço de tempos defasados a partir de séries de temperatura do ar na Reserva Biológica de Jaru - Cerino, Matheus Bruno Rodrigues (2021)
Recognized the importance of studying the dynamics of ecosystems, studies focusing on the characterization of the dynamics of the Amazon forest stand out. In this regard, effective methodologies in obtaining results that characterize this dynamic are studied. A technique that stands out in this process is that described by Takens' theorem (1981), which is efficient in characterizing the dynamics of complex systems, using only a series of data with a sufficiently strong correlation with the system. Based on previous studies developed by the Graduate Program in Environmental Physics and using air temperature data series, this study characterized the micrometeorological dynamics of the Jaru Biological Reserve. After characterization, the matrix rotation technique was used to investigate the possibility of coupling. The results pointed to the possibility, not only of reconstructing the dynamics of the ecosystem using only air temperature data, but also of inferring data from other variables, such as the liquid radiation profile. Other results refer to the relationship established between relative humidity, liquid radiation and air temperature.